Cosmopolitan memories in East Asia: revisiting and reinventing the Second World War - Soh, Changrok (International journal of transitional justice, 2014)
This article argues that the rise of associational life across East Asia in the 1990s has increasingly challenged states’ monopoly over the collective remembrance of war. Civil society actors are capturing or subverting state memory-making apparatuses, creating their own commemorative devices and using litigation to publicize the voices of forgotten victims. The activities of oppositional memory workers, although deeply concerned with local issues,1 are contributing to the formation of a body of transnational memories infused with human rights. These memories are even spreading beyond the region. However, this ongoing transcendence of East Asian war memories into cosmopolitan memory is not inevitable - ultimately the process depends on the vibrancy and openness of civil society itself.